Implantable collamer lens versus small incision lenticule extraction for high myopia correction: A systematic review and meta-analysis - Cao, Kai; Zhang, Jingshang; Wang, Jinda; Yusufu, Mayinuer; Jin, Shanshan; Chen, Shuying; Wang, Ningli; Jin, Zi-Bing; Wan, Xiu Hua (BMC ophthalmology, 2021)
Purpose To compare the efficacy, safety, predictability and visual quality between implantable collamer lens (ICL) implantation and small incision lenticule extraction (SMILE) for high myopia correction in adults. Methods A systematic review and meta-analysis was conducted. A comprehensive literature search was done based on databases including PubMed, Science Direct, Embase, and the Cochrane Central Register of Controlled Trials. The efficacy index, safety index, changes in Snellen lines of corrected distance visual acuity (CDVA), predictability (difference between post-operative and attempted spherical equivalent error, SER), incidence of halos, and change in higher-order aberrations (HOAs) were compared. Mean difference (MD) and 95% confidence interval (CI) was used to estimate continuous outcomes, risk ratio (RR) and 95%CI was used to estimate categorical outcomes. Results Five observational studies involving 555 eyes were included in this review. Studies’ sample sizes (eyes) ranged from 76 to 197. Subjects’ refraction ranged from -6 diopter (D) to -12D. Study duration of most researches were 6 months or 12 months. Compared to SMILE, ICL implantation showed better efficacy index (MD=0.09, 95%CI:0.01 to 0.16) and better safety index (MD=0.08, 95%CI: 0.00 to 0.16). Compared with SMILE, more ICL-treated eyes gained one or more Snellen lines of CDVA (RR=1.54, 95%CI:1.28 to 1.86), more gained two or more lines (RR=2.09, 95%CI:1.40 to 3.13), less lost one or more lines (RR=0.17, 95%CI:0.05 to 0.63). There was no difference in predictability between two treatments, RRs of predictability of within ±0.5D and ±1D were 1.13 (95%CI: 0.94 to 1.36) and 1.00 (95%CI: 0.98 to 1.02). Compared with SMILE, ICL implantation came with a higher risk of halos [RR=1.79, 95%CI: 1.48 to 2.16] and less increase in total HOAs (MD=-0.23, 95%CI: -0.42 to -0.03). Conclusion Compared with SMILE, ICL implantation showed a higher risk of halos, but equal performance on SER control, and better performance on efficacy index, safety index, CDVA improvement and HOAs control. Overall, ICL implantation might be a better choice for high myopia correction in adults.